Foreign Exchange Market Volatility in Eu Accession Countries in the Run-Up to Euro Adoption : Weathering Uncharted Waters - Szekely, Istvan (IMF Working Papers; Working Paper ;, 2004)
The paper analyzes foreign exchange market volatility in four Central European EU accession countries in 2001-2003. By using a Markov regime-switching model, it identifies two regimes representing high- and low-volatility periods. The estimation results show not only that volatilities are different between the two regimes but also that some of the cross-correlations differ. Notably, cross-correlations increase substantially for two pairs of currencies (the Hungarian forint-Polish zloty and the Czech koruna-Slovak koruna) in the high-volatility period. The paper concludes by discussing the policy implications of these findings.